Phenomics and genomic features of Enterococcus avium IRMC1622a isolated from a clinical sample of hospitalized patient - Reem AlJindan; Nehal Mahmoud; Doaa M. AlEraky; Noor B. Almandil; Sayed AbdulAzeez; J. Francis Borgio (Elsevier, 2024)
Background: Enterococcus avium (E. avium) is a Gram-positive nosocomial pathogen that is commonly isolated from the alimentary tract. The objective of this functional genomics study was to identify the resistant genes by analyzing the genome of E. avium IRMC1622a, a type of bacteria found in feces collected from a patient at a Saudi Arabian tertiary hospital. Methods: The bacterial strain IRMC1622a was identified by 16 S rRNA sequencing as Enterococcus sp. The resistance phenomics were performed using VITEK® 2, and morphological analysis was achieved using a scanning electron microscope (SEM). Finally, the whole bacterial genome of the bacterial strain IRMC1622a was subjected to sequencing during October 2023 using Oxford Nanopore long-read sequencing technology, and mining for resistant genes. Results: The results of antimicrobial resistant phenomics indicated that the IRMC1622a strain was sensitive to all tested antimicrobial agents except for erythromycin, and the same result was confirmed by genomic analysis in addition to other classes of antibiotics. SEM showed E. avium IRMC1622a is ovoid shape, in single cells (L 1.2797 ± 0.1490 µm), in pairs (L 1.7333 ± 0.1054 µm), and in chains (L 2.44033 ± 0.1978 µm). The E. avium IRMC1622a genome has 14 (in CARD) antimicrobial resistance genes that were identified with several mechanisms of antimicrobial resistance, such as the efflux pump and conferring antibiotic resistance. The present study revealed that the E. avium IRMC1622a genome contains a high number of genes associated with virulence factors, and 14 matched pathogenic protein families and predicted as human pathogen (probability score 0.855). We report two (ISEnfa4 and ISEfa5) mobile genetic elements for the first time in the E. avium genome. Conclusions: The study concludes that E. avium IRMC1622a is susceptible to all tested antibacterials except erythromycin. The IRMC1622a has 14 genes encoding antimicrobial resistance mechanisms, including the efflux pump and conferring antibiotic resistance. This could indicate a potential rise in E. avium resistance in healthcare facilities. These observations may raise concerns regarding E. avium resistance in healthcare. We need more research to understand the pathophysiology of E. avium, which leads to hospital-acquired infections.